2023
DOI: 10.1159/000530872
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Blood Purification with CytoSorb in 359 Critically Ill Patients

Marina Pieri,
Matteo A. Bonizzoni,
Alessandro Belletti
et al.

Abstract: Introduction: Critically ill patients with inflammatory dysregulation and organ disfunction may benefit from blood purification, although the use of this technique has not been described in large case series. We evaluated clinical outcomes and survival in high-risk intensive care unit (ICU) patients who underwent extracorporeal blood purification. Methods: 359 consecutive ICU patients treated with CytoSorb were included. Results: Main admission diagnoses were 120 (34%) refractory cardiac arrest under mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, the effect of CytoSorb® hemoadsorption on hyperinflammation remains controversial across different clinical studies. Some observational studies suggest that CytoSorb® may lower circulating cytokine concentrations and improve organ dysfunction and hemodynamics in critically ill patients with various hyperinflammatory conditions [34][35][36]. Similarly, a prospective, randomized single center study by Ingo et al showed that a significant short-term reduction in proinflammatory cytokine levels of Il-8 and TNFα at 6 h after CPB could be observed in patients receiving on-pump cardiac surgery and intraoperative CytoSorb® hemoadsorption [37].…”
Section: Rationale For Hemoadsorption Therapy In Ie Patients Receivin...mentioning
confidence: 98%
“…However, the effect of CytoSorb® hemoadsorption on hyperinflammation remains controversial across different clinical studies. Some observational studies suggest that CytoSorb® may lower circulating cytokine concentrations and improve organ dysfunction and hemodynamics in critically ill patients with various hyperinflammatory conditions [34][35][36]. Similarly, a prospective, randomized single center study by Ingo et al showed that a significant short-term reduction in proinflammatory cytokine levels of Il-8 and TNFα at 6 h after CPB could be observed in patients receiving on-pump cardiac surgery and intraoperative CytoSorb® hemoadsorption [37].…”
Section: Rationale For Hemoadsorption Therapy In Ie Patients Receivin...mentioning
confidence: 98%
“…However, the effect of CytoSorb ® hemoadsorption on hyperinflammation remains controversial across different clinical studies. Some observational studies suggest that CytoSorb ® may lower circulating cytokine concentrations, ameliorate organ dysfunction, and improve hemodynamics in critically ill patients with various hyperinflammatory conditions [34][35][36]. Similarly, a prospective, randomized single-center study by Garau et al showed that a significant short-term decrease in the proinflammatory cytokine levels of IL-8 and TNF-α at 6 h after CPB could be observed in patients undergoing on-pump cardiac surgery and intraoperative CytoSorb ® hemoadsorption [37].…”
Section: Rationale For Hemoadsorption Therapy In Ie Patients Undergoi...mentioning
confidence: 98%